A modeling method for gear transmission efficiency in transient operating conditions. (November 2020) - Habermehl, Christian; Jacobs, Georg; Neumann, Stephan
Highlights: A new method for efficiency modeling of gear transmissions. Efficiency calculation for an automotive six-speed dual-clutch transmission. Good agreement between stationary validation measurements and simulation. Transmission power losses investigated in driving cycles and during power shifts. Abstract: In this paper, a new method for efficiency modeling of gear transmissions is presented and subsequently tested on a six-speed dual-clutch transmission in a passenger car application. The method is intended to support the evaluation and optimization of transmission concepts with regard to their loss behavior in early development stages and to identify the main causes of the losses. To allow for a fast conceptual assessment through short model execution time the method is used to build a rigid-body transmission model in MATLAB/Simscape, which takes the individual component torque losses into account. Compared to existing approaches, it is thus possible to transiently determine the motion and load conditions of the individual loss sources and to include them in the overall loss calculation. In addition to the evaluation at steady state operating conditions, the power losses of transmissions in driving cycles and in particular regarding gear shifts can thus be investigated. The validation of the simulation model shows good agreement with measurements carried out on a dynamometer in a wide operating range. For the case considered the results show that the majority of the transmission losses in vehicle operation lead back to the synchronization losses of the input clutches.